Limits to partnership working: developing relationship-based approaches with children and their families. Issue 2 (3rd April 2018) - Holt, Kim; Kelly, Nancy
Abstract: Located within a context of widespread change social work professionals are required to navigate tensions between organisational imperatives and developing effective relationships with families. Achieving effective partnership working is premised on the development of relational ways of working where trust is formed through co-creation. The recent emergence of 'Fast-track' approaches in education and training reflects a shift away from developing skills in critical/analytical reflection, towards an employer-led approach that prioritises the need for 'ready practitioners'. Simultaneously there has been change in the family justice system, culminating in the Children and Families Act 2014 and the 26-week time frame for the completion of care cases. This paper explores current contradictions within social work practice. Pivotal is defining the role of social work within a contemporary English jurisdiction. Adopting deeper relational ways of working with families may help to define the boundaries of a profession that appears to have lost its identity. Rather than facing the prospect that the door is closed on the possibility of reclaiming practice that prioritises and values professional judgement and discretion, this paper reflects upon some positive examples of relational work with families by social workers within different sectors of practice.